Mindfulness: A necessary leadership competency. Issue 2 (March 2022) - Parchment, Joy
Abstract : A must-have skill, being mindful is essential for all nurses, especially in the chaotic healthcare environment. Abstract : A must-have skill, being mindful is essential for all nurses, especially in the chaotic healthcare environment.